Collaborative Learning for Enhancing Student Academic Achievement in Online Grammar Class: an Experimental Study - Setya Ariani; Nita Maya Valiantien (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2022)
Collaborative learning is an activity to work in small groups or teams that allows students to develop mutual cooperation in learning. This study aims to highlight the effectiveness of collaborative learning in improving student academic achievement. It was carried out with a quantitative method and the pretest-posttest experimental design was applied. There were sixty students participated in this study. To assess students’ achievement, online grammar pretest and posttest were distributed. In addition, collaborative learning questionnaire was administered to elicit students’ responses towards collaborative learning. Based on paired-samples t test result, it was found that the pretest and posttest mean scores were significantly different (t(59) = -5.977, p < .05). This indicated that there was a higher mean score of posttest after the implementation of collaborative activities. Most students responded that collaborative learning activities improved academic performance and team work helped them to receive input from their peers as well as provide better result in completing the tasks than working individually. It is recommended that various collaborative activities should be designed to motivate university students in learning grammar.